A RETROSPECTIVE STUDY OF THE CLINICAL PROFILE OF SEVERE MALARIA CONDUCTED AT A TERTIARY CARE CENTRE IN INDIA AMONG CHILDREN AND ADULTS. - Wakil Paswan; Kumar, Dr. Kamlesh (Student's Journal of Health Research Africa, 2023)
Objectives Despite declining malaria cases, it remains a public health concern in our country, prompting an investigation into the changing clinical and epidemiological profile, especially the severity of vivax malaria, among adult patients in an Indian tertiary health-care centre. The study aims to explore the changing clinical and epidemiological profile of malaria, specifically the emergence of severe complications in vivax malaria, among adults in an Indian tertiary health-care centre. Methods A longitudinal observational research was undertaken, encompassing adults and children diagnosed with Plasmodium vivax, P. falciparum, or mixed malarial infections from a tertiary care centre in A. N. M. Medical College, Gaya, Bihar, India through rapid diagnostic tests or peripheral smear. Results Involving 147 patients, the study revealed vivax as the most prominent species (62 %), after which falciparum showed the next highest number of cases encompassing 29 % of the population. Mixed plasmodium species was identified to affect only 9 % of the study population. The average patient age was 34.13 years, comprising 64 % men and 36 % women. Notably, 23 % of patients exhibited clinical manifestations of malaria, at least a single symptom. Patients with P. vivax demonstrated significantly higher rates of severe anaemia (hemoglobin lesser than 5 mg per dl), acute kidney injury, and thrombocytopenia (platelet count lesser than 1 lac/cmm). Additionally, comorbid illnesses were present in a substantial portion (32 %) of the malaria affected individuals. Conclusion The predominant cause of malaria cases is attributed to P. vivax, raising concerns about its potential to induce life-threatening illnesses. Further exploration into the influence of comorbid conditions on malaria's clinical outcomes is warranted. Recommendation The study recommends for broader multicentric clinical and epidemiologic investigations to deepen our understanding of malaria's pathogenesis and drug resistance, emphasizing the need to implement comprehensive strategies for alleviating the country's malaria burden.